https://doi.org/10.36873/ UPAYA MENINGKATKAN PATOGENISITAS Lecanicillium lecanii TERHADAP HAMA PENGISAP POLONG KEDELAI Riptortus linearis melalui REGULASI KITINASE DAN UJI KOMPATIBILITAS PESTISIDA: Efforts to Increase The Pathogenicity of Lecanicillium lecanii Against Soybean Sucking Pest Riptortus Linearis Through Chitinase Regulation and Pesticide Compatibility Tests - Yayuk Mulyati (AgriPeat, 2021)
The aim of this study was to increase the killing power of Lecanicillium lecanii through (1) regulation of chitinase synthesis and (2) finding compatible pesticides to be applied together with L. lecanii. Analysis of the role of chitinase on the pathogenicity of L. lecanii was carried out through the selection of basal media composition, optimization of culture conditions (media pH, temperature and incubation period), and bioassay against soybean pod sucking pest Riptortus linearis. Meanwhile, the compatibility test of fungi with pesticides was carried out by growing the fungus on PDA media added with fungicides with the active ingredients of carbendazine, triadimefon, methyl thiophanate, kaptan, iprodion, and mankozeb. The results showed that L. lecanii grown on I basal media, pH 5, temperature 30 oC, and an incubation period of 5 or 6 days was able to optimally increase chitinase activity. Bioassays on R. linearis showed a mortality of up to 80% at 3 days after application. The pathogenicity of L lecanii in this study is much more significant than in previous research reports. In the second study, the compatibility test with pesticides showed that L. lecanii was compatible with pesticides with the active ingredients of mancozeb. Pesticides with the active ingredients of kaptan, iprodione, carbendazine, triadimefon, and methyl thiophanate are toxic (strongly inhibit) the growth of L. lecanii colonies. The two findings of this study indicate that L. lecanii has good prospects as a bioinsecticide in terms of increasing its pathogenicity and compatibility with pesticides